Pinus caribaea - Lamb, A (Commenwealth Forestry Institute, University of Oxford, 1973)
Since Hi1mar Luckhoff (1964) started his work in 1957 on the variation and behaviour of Pinus caribaea in its natural habitats and in subtropical South African plantations, this pine has become the most important lowland timber tree being planted in tropical countries, because tropical foresters have come to realise that this is a pine capable of growing at sea level on poor infertile sites even at the equator...